Analisis Pengaruh Karakteristik Dewan Terhadap Asymmetric Cost Behavior pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018 - Supriyanto Supriyanto (Pusat P2M Politeknik Negeri Batam, 2021)
Analyzing the effect of the board characteristics on asymmetric cost behavior is the aim of this study. Asymmetric cost behavior is dependent variable, while board characteristics are an independent variable in which there are changes in sales, decrease dummy, interaction term, the board size, and non-executive ratios. In addition, the control variable is owned by institutional ownership. The data population was 1570 data obtained from 314 companies listed on the Indonesia Stock Exchange in 2014-2018. Data samples that had been tested and experienced deviations were 336 samples, therefore, the number of data analyzed is equal to 1234 samples. The annual financial statements were used in this study as secondary data and quantitative research. The result of the study is board characteristics have significant positive effect of changes in sales and interaction terms on asymmetric cost behavior and significant negative effect of decrease dummy on asymmetric cost behavior. The non-significant variable has negative effect on board size and institutional ownership on asymmetric cost behavior, while the ratio of non-executive has positive non-significant effect on asymmetric cost behavior.